Modified Bentall procedure with mitral valve replacement in a patient with Marfan syndrome: a case report - Raha, Sanjay K.; Barua, Sumit; Kamrul Hasan, M.; Shafiqul Islam, M.; Jobaid Hasan, M.; Faisal N. Majumder, N.; Al-Faraby, Mahmodul H.; Roy, Kaushik; Sorower Hossain, M.; Biswas, Smriti K.; Jahan, Hosne (International Journal of Research in Medical Sciences, 2024)
Marfan syndrome (MFS) is an autosomal dominant connective tissue disorder characterized by fibrillin-1 protein abnormalities, predisposing individuals to cardiovascular complications such as aortic root dilation and mitral valve prolapse (MVP). Management often requires surgical intervention, with the modified Bentall procedure being a standard approach for aortic root replacement. However, managing concomitant mitral valve pathology poses additional challenges due to the complex anatomical relationship between the two valves and the prolonged nature of the procedure. We present a case report of a 35-year-old male with Marfan syndrome who underwent a successful simultaneous modified Bentall procedure and mitral valve replacement for concurrent aortic root aneurysm and mitral valve prolapse. Surgical interventions involved meticulous attention to detail to mitigate risks associated with malpositioned coronary ostial sutures, debridement of the severely calcified mitral valve, and achieving hemostasis. Following surgery, the patient exhibited favorable postoperative outcomes, with evidence of optimal valve function and improved systolic and diastolic parameters, indicative of a successful recovery.